Apply GIS, Fuzzy Theory and AHP to Determine Land Value for Land Valuation: A Case Study of Dong Anh District, Hanoi - Cuong, Doan Quang; Van Tuan, Tran; Thi Kieu Trang, Trinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 38 No 4, 2022)
The land valuation process is an integrated assessment of land price determinants that help managers formulate land-use policies, taxes, and the real estate market. In this study, ten factors affecting land value are selected and divided into 03 groups of factors, including i) Accessibility; ii) Environment; and iii) Socio-culture. The study then determined the weights of the elements by AHP and performed the spatial analysis by GIS, Fuzzy, to determine land value. The results reflect the distribution of land value zones in the Dong Anh district and show a strong correlation with the actual land prices traded in the market. This land value information is assigned to the land parcels to support automated valuation models and urban planning. This study can be implemented in other areas or on a larger scale.